Cavity-enhanced high-order harmonic generation for high-performance time-resolved photoemission experiments - Thomas K. Allison; Alice Kunin; Gerd Schönhense (APL Photonics)
Recent breakthroughs in high repetition-rate extreme ultraviolet (XUV) light sources and photoelectron analyzers have led to dramatic advances in the performance of time-resolved photoemission experiments. In this perspective article, we discuss the application of cavity-enhanced high-order harmonic generation, with repetition rates exceeding 10 MHz, to photoemission experiments using advanced endstations incorporating time-of-flight photoelectron analyzers. We discuss recent results, perspective on future areas for further technological improvement, and the wide array of science enabled by ultrafast XUV photoemission experiments, now in a qualitatively new regime.